Development of a telehealth obesity OSCE and reliable checklist for assessment of resident physicians: a pilot study - Natalie A. Cameron; Robert F. Kushner (BMC Medical Education, 2022)
Abstract Background Obesity is a major public health problem, yet residents undergo little formal training and assessment in obesity-related care. Given the recent growth of telehealth, physicians must further learn to apply these skills using a virtual platform. Therefore, we aimed to develop an objective structured clinical examination (OSCE) with reliable checklists to assess resident ability to take a patient-centered obesity-focused history that was feasible over telehealth based on published obesity competencies for medical education. Methods We developed a 15-minute telehealth OSCE to simulate an obesity-related encounter for residents modified from a script used to assess medical student obesity competencies. We designed three checklists to assess resident skills in history taking, communication and professionalism during the obesity-related encounter. Resident performance was assessed as the percentage of obesity-related history taking questions asked during the encounter and as the mean communication and professionalism scores on a scale of 1 through 5 with 1 representing unacceptable/offensive behavior and 5 representing excellent skills. Encounters and assessments were completed by two commissioned actors (standardized patients) and 26 internal medicine residents over a secure online platform. We assessed the reliability of each checklist by calculating the percent agreement between standardized patients and the kappa (κ) statistic on each checklist overall and by each checklist item. Results Overall agreement between standardized patients on the history taking, communication and professionalism checklists were 83.2% (κ = 0.63), 99.5% (κ = 0.72) and 97.8% (κ =0.44), respectively. On average, residents asked 64.8% of questions on the history taking checklist and scored 3.8 and 3.9 out of 5 on the communication and professionalism checklists, respectively. Conclusions Results from this pilot study suggest that our telehealth obesity OSCE and checklists are moderately reliable for assessing key obesity competencies among residents on a virtual platform. Integrating obesity OSCEs and other educational interventions into residency curricula are needed to improve resident ability to take an obesity-focused history.